Urban Loopholes Creative Alliances of Spatial Production in Shanghai’s City Center - Zhou, Ying (Birkhäuser, 2017)
Ein strategisches Bündnis von städtischer Umnutzung, Kreativwirtschaft, Konsumökonomie und Denkmalschutz hat eine bemerkenswerte Transformation innerstädtischer Quartiere in Shanghai geschaffen. In einer Verbindung von intimen Kenntnissen der lokalen Szene und kritischer Distanz entwirft die Autorin ein genaues Bild der Strategien, Akteure und Prozesse eines spezifisch chinesischen Modells städtischer Transformation. Konzepte wie "urbane Fluchten", "Erhalten durch Bewohnen" und "Gentrifizierung in Chinesischer Manier" werden als charakteristisch für die Mechanismen dieser Stadtentwicklung Vorgestellt. Urban Loopholes führt die Unverzichtbarkeit der Resilienz urbaner Räume gegenüber dem Veränderungsdruck der Globalisierung vor Augen. Urban reuse, creative production, consumerism, and heritage protection have formed an alliance for the transformation of inner-city districts of Shanghai. This in-depth study, based on the author’s intimate familiarity of the local scene and supplemented by her critical outsider’s insights, describes the strategies, players, and processes of a uniquely Chinese model of urban transformation. Concepts like "Urban Loopholes", "Preservation via inhabitation", and "Gentrification with Chinese characteristics" characterize the specific mechanisms for urban development in Shanghai. Urban Loopholes invites the reader to rethink the necessity of urban resilience in the face of globalization’s impact for change
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Jun 2017)
Keywords: Geschichte 1992-; Stadtplanung; Schanghai